2019
DOI: 10.1088/2516-1083/ab59be
|View full text |Cite
|
Sign up to set email alerts
|

Solar soft cost ontology: a review of solar soft costs

Abstract: The continued deployment of renewable energy is critical to the energy transition necessary for climate change mitigation. Since cost is one of the primary drivers of solar adoption, we must continue to reduce the cost of solar to hasten the transition to clean energy. Currently, solar soft costs account for 52%-70% of the cost of an installed residential solar photovoltaic (PV) system in the U.S. These costs are persistent and an increasing share of the costs, since hardware costs continue to decline. The con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…The same types of studies can be found for photovoltaics, where taxonomies have been proposed for both cost and maintenance analysis. In the first group-cost-it is possible to mention the works carried out at the National Renewable Energy Laboratory (NREL) [15,16] for cost benchmarking and [17] focused on soft costs for Photovoltaics (PV). The second group, maintenance, presents a detailed breakdown of aspects related to photovoltaic energy that have been developed in [18] and the Trust PV project [19], to analyse the risk and maintenance aspects in the whole PV value chain.…”
Section: State Of the Artmentioning
confidence: 99%
“…The same types of studies can be found for photovoltaics, where taxonomies have been proposed for both cost and maintenance analysis. In the first group-cost-it is possible to mention the works carried out at the National Renewable Energy Laboratory (NREL) [15,16] for cost benchmarking and [17] focused on soft costs for Photovoltaics (PV). The second group, maintenance, presents a detailed breakdown of aspects related to photovoltaic energy that have been developed in [18] and the Trust PV project [19], to analyse the risk and maintenance aspects in the whole PV value chain.…”
Section: State Of the Artmentioning
confidence: 99%